(untitled) (Research, Society and Development, 2023)
For a long time, teachers had the expository class as the only and exclusive method to teach a certain object of knowledge (content). In the middle of the 21st century, a time of social, political, economic, cultural and, mainly, educational transformations, this didactic-methodological strategy is considered retrograde, archaic, traditional. In this sense, there is a need to create new techniques that help both the teacher’s teaching and the development of student learning, such as movement and virtual reality. The use of virtual reality is justified in scientific and educational applications constantly. The potential influence of movement on children’s academic performance is sometimes underestimated, however, like VR, movement is an interdisciplinary teaching method that stimulates several areas of the human brain at the same time. Therefore, this article aims to establish an interrelation between movement, learning and virtual reality as important didactic strategies at the service of teaching and learning. To achieve the scope of the work, we carried out a predominantly qualitative narrative review of the proposed theme. We evidenced according to studies that these methods contribute to the increase of the student’s interest, motivation and learning; favors collective work, in collaborative teams, with the potential to stimulate social skills and greater engagement of students.